The Use of Ketamine in Traumatic Brain Injury - Firdaus, Riyadh; Natanegara, Ahmad Pasha; Sutedja, Anasthasia D.; Kartika, Gloria (Jurnal Neuroanestesi Indonesia, 2025)
Ketamine, initially developed as an anesthetic agent, has gained significant attention for its potential therapeutic effects in various neurological conditions, particularly in patients with traumatic brain injury (TBI). The use of ketamine is controversial, especially due to concerns that it may increase intracranial pressure in patients with TBI. In this case report, a 29-year-old male with a diagnosis of severe head injury complicated by hemorrhagic shock from multiple traumas presented with decreased consciousness, active bleeding from the extremities, and hemodynamic instability. Rapid Sequence Intubation (RSI) was performed, during procedure which the patient was administered ketamine at a dose of 1 mg/kg, lidocaine 1.5 mg/kg, and rocuronium at 1 mg/kg. Fluid resuscitation with 1000 ml of crystalloid solution and norepinephrine drip 0.1 mcg/kg/min was also initiated. Post-resuscitation, the patient's hemodynamics were monitored and found stable. A literature search revealed systematic reviews from 2020 and studies from 2022 that focused on outcomes related to intracranial pressure and mortality in TBI patients receiving ketamine. The use of ketamine did not demonstrate evidence of harm in patients with traumatic head injury.